The grid method Beziers – d'Arcy-Thompson in the reconstruction of morphogenesis and abiogenesis: elementary biomimetic model - Gradov O.V. (Морфологія, 2011)
We propose a new modification made in the morphology of biological imaging methods based on new types of components and nets. Shown its applicability not only in the comparative morphology and evolutionary and systematic, but also in abiogenetic studies. An approach of deterministic or directed transformation of the grid, allowing to control the result of process according to its trend. Its been made the transition from a purely geometric («CAD») to model «CAE» - analysis of the structure affecting distorting factors. We propose a method for detecting deformations of the lattice for subsequent blending with computer engineering biomimetic structures. Showing the limitations of the theory of transformation by d'Ar-cy-Thompson-sampling and scaling of the original signal. A system for gel documentation reaction-diffusion processes, si-mulate-regulating morphogenesis in partially ordered media that displays the result on the PC for 3D-visualization of the perturbed transformation of the grid. Using this method showed the presence of nonlinear pulse waves and currents in the active medium in the photoinduced assembly of artificial cells. Based on the methods of computer optics developed a method of forecasting the likely strains of the simplest artificial cells.